Fabrication of tissue engineering scaffold from poly(vinylalcohol-co-ethylene)/poly(D, L-lactic-co-glycolic acid) blend: Miscibility, thermomechanical properties, and morphology. Issue 10 (2nd July 2016) - Aouak, Taieb; Ouladsmane, Mohamed; Alghamdi, Abdulaziz Ali; Al-Owais, Ahmad Abdulaziz; Al-Turki, Turki Mohammad; Alothman, Zeid Abdullah; Saeed, Waseem Sharaf
ABSTRACT: A series of poly(DL-lactide- co -glycolic acid) (PLGA) with poly(vinylalcohol- co -ethylene) (PEVAL) blends were prepared by solution casting method. The miscibility, thermal and mechanical properties have been investigated using FTIR, DSC, and DMA techniques. The miscibility of this pair of polymers throughout compositions was proved by these methods through the single Tg and the presence of interactions between the constituents. The TGA analysis revealed three degradation zones and no sensible enhancement in the thermal stability of PLGA was noted with addition of PEVAL content. The SEM analysis revealed that the draying method dramatically influence the surface morphology of copolymers and blend. The cross section micrograph of blend scaffold containing 50 wt% of PEVAL presents microcavities of diameter pores ranged between 70 and 170 µm interconnected and uniformly distributed in the polymer matrix. GRAPHICAL ABSTRACT: